Knowledge about simulation and frequency of use in the teaching of the subject Human Morfophisiopatology I - Pavel Vigo Cuza; Arnovis Baluja Echevarria; Alenia Matos González (Medisur)
Background: The use of simulation can accelerate the learning process and helps to raise standards. Its use must have a logical sequence in the calendar plan of the subject that corresponds to the needs and requirements of the curriculum and analytical programs of the different subjects. Objective: to characterize the knowledge about the simulation and the frequency with which it is used as a resource for teaching Human Morfophisiopatology I National Training Program in Integrative Medicine Community. Methods: Research in theoretical methods were used, allowing the bibliographic review, documentary, and the analysis and synthesis that supports the study. A questionnaire was administered to 85 teachers related to teaching practice of the subject and an interview with five key informants. We characterized the knowledge of teachers on the simulation. Results: Only 63.3% knew the method of simulation and they used 87, 04%. The frequency of use of simulation in teaching of the subject showed that 51.06% of teachers have always used this resource, while only 36.17% use it most of the time. Conclusion: Not all teachers know the simulation is used in teaching or recognize its value in the teaching - learning of the subject Human Morfophisiopatology I.